2007
DOI: 10.1111/j.1600-0625.2007.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyfullerenes localize within mitochondria and prevent the UVB‐induced intrinsic apoptotic pathway

Abstract: Carboxyfullerenes (CF) act as free radical scavengers in many cell settings and prevent apoptosis in vitro and in vivo. CF protect normal human keratinocytes from UVB-induced apoptosis, although the mechanisms underlying this effect remain to be clarified. Double-staining confocal laser microscopy revealed that CF penetrate the cell and colocalize with cytokeratin-18 within cytoplasm. This localization was confirmed by transmission electron microscopy that showed CF intermingled with keratin filaments. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 51 publications
8
48
0
Order By: Relevance
“…However, results suggest that blocking ROS using FDs in response to an immune complex (a FcεRIIA-dependent stimuli [50] ) parallels inhibition of mediator release. This is in line with previous work suggesting that FDs interfere with the generation of mitochondrial-derived ROS [51,52] .…”
Section: * Fullerenes Inhibit Inflammation Caused By Arthritissupporting
confidence: 82%
“…However, results suggest that blocking ROS using FDs in response to an immune complex (a FcεRIIA-dependent stimuli [50] ) parallels inhibition of mediator release. This is in line with previous work suggesting that FDs interfere with the generation of mitochondrial-derived ROS [51,52] .…”
Section: * Fullerenes Inhibit Inflammation Caused By Arthritissupporting
confidence: 82%
“…This type of cell demise is characterized by activation of the caspase enzyme family and fragmentation of DNA, which occurs without plasma membrane breakdown and is followed by recognition and removal of apoptotic cell by phagocytes in the absence of inflammation [107]. This is consistent with the preferential mitochondrial localization of water-soluble C 60 derivatives [67,68], having in mind that ROSinduced mitochondrial dysfunction is a key initial step in the ''mitochondrial'' pathway of apoptosis [107]. Interestingly, polyhydroxylated C 60 was able to suppress proliferation and induce apoptosis of tumor cells in the absence of photosensitization and ROS production [88,108,109].…”
Section: Anticancer and Antimicrobial Activitymentioning
confidence: 71%
“…An important feature of various C 60 preparations that facilitates their biological reactivity is the ability to penetrate cell membrane and gain access to cell cytoplasm, organelles and nucleus, as predicted by theoretical studies and confirmed in various experimental settings [67][68][69][70][71]. Singlet oxygen, generated by energy transfer from C 60 to molecular oxygen (Type II photochemical mechanism), could directly react with various biological targets, including lipids, proteins, nucleic acids and carbohydrates, resulting in cell damage or functional alterations [8].…”
Section: Ros-dependent Biological Effects Of C 60mentioning
confidence: 96%
“…1A). BAD was reported to play a critical role in radiation-induced apoptosis (26)(27)(28) and was also found to be an important mediator involved in AF1q regulation of doxorubicin-induced apoptosis (24). Therefore, we hypothesized that BAD is also involved in the AF1q enhancement of radiation-induced apoptosis.…”
Section: Af1q Enhancement Of Radiation-induced Apoptosis By Upregulatmentioning
confidence: 95%